1998
DOI: 10.1038/29542
|View full text |Cite
|
Sign up to set email alerts
|

Stress and glucocorticoids impair retrieval of long-term spatial memory

Abstract: Extensive evidence from animal and human studies indicates that stress and glucocorticoids influence cognitive function. Previous studies have focused exclusively on glucocorticoid effects on acquisition and long-term storage of newly acquired information. Here we report that stress and glucocorticoids also affect memory retrieval. We show that rats have impaired performance in a water-maze spatial task after being given footshock 30 min before retention testing but are not impaired when footshock is given 2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

50
576
9
7

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,039 publications
(642 citation statements)
references
References 16 publications
50
576
9
7
Order By: Relevance
“…The possibility of unavoidable exposure to stress during early development of the HR and LR lines cannot be excluded. Chronically elevated corticosteroid levels have adverse effects on learning and memory (Starkman et al, 2001) and memory retrieval is severely impaired by exposure to short-term elevation of corticosteroid levels when administered prior to testing (de Quervain et al, 1998). In the present study the fish were not subject to any stressors before, during or after conditioning, other than the acute stressor (emersion + confinement) used for conditioning itself.…”
Section: Discussionmentioning
confidence: 97%
“…The possibility of unavoidable exposure to stress during early development of the HR and LR lines cannot be excluded. Chronically elevated corticosteroid levels have adverse effects on learning and memory (Starkman et al, 2001) and memory retrieval is severely impaired by exposure to short-term elevation of corticosteroid levels when administered prior to testing (de Quervain et al, 1998). In the present study the fish were not subject to any stressors before, during or after conditioning, other than the acute stressor (emersion + confinement) used for conditioning itself.…”
Section: Discussionmentioning
confidence: 97%
“…By contrast, memory retrieval tends to be impaired following a stressor (Buchanan et al, 2006;de Quervain et al, 1998;. These effects are specific to stressors that result in increased corticosteroid release.…”
Section: Discussionmentioning
confidence: 99%
“…Stress after learning can improve memory consolidation (see Roozendaal, 2000 for review). By contrast, stress before memory testing can impair memory retrieval performance (Buchanan, Tranel, & Adolphs, 2006;de Quervain, Roozendaal, & McGaugh, 1998;Kuhlmann, Piel, & Wolf, 2005). Roozendaal and colleagues have documented that these differences in the effects of stress on the different phases of memory are dependent on the amygdala.…”
Section: Introductionmentioning
confidence: 99%
“…One explanation for our null retrieval findings may be that although the stress induction elevated cortisol enough to facilitate consolidation, levels were not high enough to exert a detrimental effect on retrieval. Support for this comes from a study by de Quervain et al (1998), which showed that the impairing effect of systemic corticosterone administration on retrieval in rats was dose dependent. Pharmacological studies certainly induce a much higher cortisol response than do stress studies, possibly accounting for impaired retrieval findings in these studies.…”
Section: Discussionmentioning
confidence: 99%